Pengaruh Proses Transnasionalisasi Coffehouse Company “Starbucks Coffee” Terhadap Budaya Tradisional Minum Teh di China - Wahyuwanti, Rena Anisah (Jurnal Transformasi Global, 2022)
ABSTRACT The phenomenon of globalization has dominated various aspects of human life today. Globalization has changed the patterns of human interaction and activities to be faster, more modern, and more innovative. In the economic aspect, globalization has led to the process of economic transnationalism, where TNCs and MNCs have become key players in the global flow of goods and services in various sectors. These transnational corporations are able to create new, modern, and exclusive consumerist trends that attract everyone and make them want to follow them. This is what happened to the trend of coffee drinking, which has now become a global coffee culture, one of which is pioneered by Starbucks Coffee Company. The presence of Starbucks Coffee Company in various countries around the world, including China, is predicted to be a challenge to the existence of local culture, such as the traditional culture of drinking tea in China, which has been a long-standing tradition. This paper will analyze the influence of Starbucks on the traditional culture of drinking tea in China using the concept of Globalization and Three H Scenario. The results of the analysis show that Starbucks has been able to internalize the modern values of coffee drinking culture and change the perception of the Chinese people, who previously only oriented themselves towards tea, to now consume coffee, and gradually Starbucks can displace the traditional culture of drinking tea in China. Keywords: Transnasionalisasi, Starbucks, Three H Scenario, Budaya Minum Teh